ANALYZING THE IMPACT OF HALAL TOURISM DEVELOPMENT IN TAMBORASI ON THE MICROECONOMIC CONDITIONS OF LOCAL COMMUNITIES - Abdul Wahid Mongkito; Alda Tri Utami; Alfian Toar (Referensi Islamika: Jurnal Studi Islam, 2026)
This study aims to analyze the development strategy of Tamborasi River halal tourism, examine its impact on the microeconomic conditions and welfare of local communities in Tamborasi Village, and explore the tourism development strategy from an Islamic perspective. This research employed a qualitative descriptive approach. The collected data were analyzed using descriptive qualitative analysis to identify tourism development strategies, economic impacts, and the implementation of Islamic values in tourism management. The research results show that Tamborasi River tourism has significant potential for further development due to its unique appeal as the world's shortest river, supported by adequate infrastructure and effective promotional strategies. Tamborasi River tourism development offers promising potential for businesses, with revenues that can continue to grow along with increasing visitor numbers. From an Islamic perspective, the tourism development strategy emphasizes the provision of worship facilities, halal food services, environmental cleanliness, and quality services based on sharia principles. The findings imply that the development of Tamborasi River halal tourism can serve as a strategic instrument for strengthening local economic activities through the empowerment of MSMEs, job creation, and community participation. The study also highlights the importance of improving Muslim-friendly tourism facilities, strengthening halal certification support for local businesses, and enhancing collaboration among local governments, tourism managers, and community stakeholders to ensure sustainable and inclusive halal tourism development. This study contributes to the literature on halal tourism development by integrating microeconomic community impacts with Islamic tourism principles in the context of a unique coastal tourism destination. The research also provides practical insights for policymakers and tourism managers in developing sustainable and community-based halal tourism destinations.